Strength prediction of hollow reinforced concrete beam - Mohd Sabree Fadzlee, Jaffri (2012)
Nowadays, price of Construction materials was increase. That is one of important factor in order to reduce the construction cost. One method in reducing this cost is by removing the concrete volumes in structure element, for example hollow section beam. An empty space that left can be used for various functions especially in building finishing. The space can be used as a route of electrical wire or as a route for ventilation system. One of the problems encountered in this idealization is the strength prediction of beam after the concrete volume has been removed. This study will investigated the effect of cavity introduced in rectangular concrete beam on its bending as well as its maximum stress. Besides that this study also wants to determine an optimum size of cavity in rectangular concrete beam that can be provided. Several high of cavity will be considered and analysed using LUSAS. There are 10 models analysed using LUSAS modeller include one solid beam as a control model. Based on the results, an optimum cavity size that can be provided in a rectangular hollow concrete beam having size 200mm x 350mm x 2000mm was 135 mm. It's because the maximum stress obtains is almost same as obtain from solid beam. As a conclusion, the maximum stress will increase with increasing a cavity size in a hollow rectangular concrete beam.